2011
DOI: 10.1177/1545968311418675
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Stroke Survivors Benefit From High-Intensity Aerobic Treadmill Exercise

Abstract: This trial demonstrates that TAEX effectively improves cardiovascular fitness and gait in persons with chronic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
182
8
10

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(211 citation statements)
references
References 47 publications
7
182
8
10
Order By: Relevance
“…47 There are a number of mechanisms which may explain the impact of exercise on social participation. Exercise can improve mobility 48 , balance, fatigue and endurance after stroke 49 , which may enable the stroke survivor to engage in activities. Physical activity is also known to improve a number of the secondary effects of stroke which may be a barrier to social participation.…”
Section: Discussionmentioning
confidence: 99%
“…47 There are a number of mechanisms which may explain the impact of exercise on social participation. Exercise can improve mobility 48 , balance, fatigue and endurance after stroke 49 , which may enable the stroke survivor to engage in activities. Physical activity is also known to improve a number of the secondary effects of stroke which may be a barrier to social participation.…”
Section: Discussionmentioning
confidence: 99%
“…43 The fact that the total duration of MICT has been at least 8 weeks among the studies that found positive effects on VO2peak may also support this notion. 97,98,100,101,[103][104][105][106][107][108][109][110] On the other hand, the application of HIIT in stroke rehabilitation appears to be sparse Given that exercise prescriptive variables were similar between studies (4 x 4-minute work 13 periods at an intensity between 85 -95% of peak heart rate, interspersed with 3-minute rest periods), one may speculate that inter-study differences in subject characteristics The underlying mechanisms for the HIIT-and MICT-mediated improvement in VO2peak in those with stroke remain to be determined but could perhaps be attributable to an enhanced ability of the skeletal muscles to utilize O2 via improved mitochondrial function. 100 However, in view of the current literature, the use of MICT appears to be more promising than HIIT for improving aerobic fitness and health outcomes among stroke patients.…”
Section: Strokementioning
confidence: 99%
“…Improved aerobic fitness would also, for the most part, reduce the symptoms of any such associated CVD and subsequently improve general health, wellbeing, and quality of life. 29,31,33,97,98,100,101,107 Based on these considerations, it seems more meaningful to determine the optimal HIIT prescriptive variables for CVD populations with respect to improving VO2peak rather than ameliorating any other symptoms and risk factors associated with a specific pathology. and subsequently prove beneficial with respect to the prevention/management of any such symptoms associated with cardiac pathologies.…”
Section: Exercise Prescriptive Variablesmentioning
confidence: 99%
“…o 2 at the end of the training intervention compared with the control group. Globas and colleagues 173 compared a 3-month progressive, high-intensity aerobic treadmill exercise intervention (n=18) with a conventional care physical therapy group (n=18). Results suggested that high-intensity treadmill training facilitates greater improvements in peak V .…”
Section: Chronic Phase Of Stroke Recoverymentioning
confidence: 99%